The in-between in writing: a matter of detour (Palíndromo, 2021)
This text reflects on some artist writing principles in the academic scope, emphasizing the importance of mobilizing the middle, which is understood here as a notion in which emerges the slips in between beginning and end, theory and practice, myself and the other, clarity and obscurity, determinations and indeterminations, demarcations and unfinished, in order to follow the thought movements. The detour and the drift arise as a methodology, which is kind of a disorderly principle that expects a writing that is able to promote an experience and dialog with oblique movements of the artistic process.
Keywords: artist writing; detour; drift